Merkel Cell Carcinoma Metastasis to the Pancreas: Report of a Rare Case and a Review of the Literature - Bhardwaj, Neil; Haiart, Sebastien; Kanhere, Harsh A; Maddern, Guy J (JOP. Journal of the Pancreas, 2014)
Context Merkel cell carcinoma is a rare skin tumour which can metastasise to regional lymph nodes and occasionally to distant organs. Merkel cell carcinoma metastasis to the pancreas has been rarely reported Case report We describe the case of Merkel cell carcinoma metastasis to the pancreas and review the literature on this rare phenomenon. Conclusion Merkel cell carcinomas metastasis should be considered as a differential in patients who present with a pancreatic mass with a previous history of Merkel cell carcinomas. Image: Large mid-pancreatic body mass.